2015
DOI: 10.3928/19404921-20141121-01
|View full text |Cite
|
Sign up to set email alerts
|

The Meanings Caregivers Ascribe to Dementia-Related Changes in Care Recipients: A Meta-Ethnography

Abstract: The number of individuals with dementia is increasing dramatically around the world, and because of this growth, an increase in the number of caregivers has occurred as well. Caregiving is often associated with negative outcomes (e.g., burden, depression, impaired physical health). These problems persist although much effort has been put into understanding caregiver strain. Some work has addressed the meanings caregivers ascribe to dementia-related changes, which may provide a better understanding of caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The strategies presented by these African-American caregivers provide valuable insight into the complex interplay between the caregiver and the person with dementia, as symptoms of dementia appear and reappear, fundamentally altering long-established patterns in the relationship. The perplexing and distressing nature of the changes shared by participants in this study echo the findings of previous studies (Evans & Lee, 2014; Large & Slinger, 2015; Lindauer & Harvath, 2015). Taken together, these studies suggest that as the person with dementia becomes increasingly impaired, caregivers experience profound grief and a struggle to redefine and reintegrate their shifting reality.…”
Section: Discussionsupporting
confidence: 87%
“…The strategies presented by these African-American caregivers provide valuable insight into the complex interplay between the caregiver and the person with dementia, as symptoms of dementia appear and reappear, fundamentally altering long-established patterns in the relationship. The perplexing and distressing nature of the changes shared by participants in this study echo the findings of previous studies (Evans & Lee, 2014; Large & Slinger, 2015; Lindauer & Harvath, 2015). Taken together, these studies suggest that as the person with dementia becomes increasingly impaired, caregivers experience profound grief and a struggle to redefine and reintegrate their shifting reality.…”
Section: Discussionsupporting
confidence: 87%
“…Qualitative research has suggested that these various appraisals and reactions to change are closely interlinked (Boylstein & Hayes, 2012;Chesla et al, 1994;Hayes et al, 2009;Kaplan, 2001;Lindauer & Harvath, 2015;Walters et al, 2010). For example, perceiving that the person with dementia is no longer the person one married could understandably undermine the feelings of love and intimacy, and both might, in turn, contribute to a sense that the relationship has been transformed into a non-marital relationship between a care-giver and a care-receiver.…”
Section: Relationship Continuity As a Framework For Linking And Measumentioning
confidence: 99%
“…Caring for one of the world’s 47 million adults with Alzheimer disease or a related dementia can be both rewarding and taxing for family members [1,2]. For some, caregiving can have detrimental effects on their mental health, leading to depression and a sense of burden [3].…”
Section: Introductionmentioning
confidence: 99%